Connecting the dots between brand experience and brand loyalty: The mediating role of brand personality and brand relationships - Ramaseshan, Balasubramani; Stein, Alisha (Palgrave Macmillian Lid., 2014)
This article critically examines consumer–brand relationships from the perspective of interpersonal relationship theory. Specifically, the authors investigate the relationship between brand experience and the two components of brand loyalty, namely purchase brand loyalty and attitudinal brand loyalty. The study also examines the link between brand experience and brand relationship variables, brand trust, brand attachment and brand commitment. In addition, the mediating role of brand personality and brand commitment in the relationship between brand experience and brandloyalty is investigated. Drawing on the results of an empirical cross-brand study from three product categories, the authors demonstrate that brand experience, brand personality and brand relationship variables (brand attachment and brand commitment) all affect the degree to which a consumer is loyal to a brand. On the basis of the findings, the authors offer guidelines to managers on how to build and sustain purchase and attitudinal brand loyalty by enhancing brand experience. The theoretical and managerial significance of the findings together with directions for future research are discussed.